Cardiac medication prescribing and adherence after acute myocardial infarction in Chinese and South Asian Canadian patients - King Kathryn M; Quan Hude; Palepu Anita; Grubisic Maja; Lai Emily J; Khan Nadia A (BMC Cardiovascular Disorders, 2011)
Abstract Background Failure to adhere to cardiac medications after acute myocardial infarction (AMI) is associated with increased mortality. Language barriers and preference for traditional medications may predispose certain ethnic groups at high risk for non-adherence. We compared prescribing and adherence to ACE-inhibitors (ACEI), beta-blockers (BB), and statins following AMI among elderly Chinese, South Asian, and Non-Asian patients. Methods Retrospective-cohort study of elderly AMI survivors (1995-2002) using administrative data from British Columbia. AMI cases and ethnicity were identified using validated ICD-9/10 coding and surname algorithms, respectively. Medication adherence was assessed using the 'proportion of days covered' (PDC) metric with a PDC ≥ 0.80 indicating optimal adherence. The independent effect of ethnicity on adherence was assessed using multivariable modeling, adjusting for socio-demographic and clinical characteristics. Results There were 9926 elderly AMI survivors (258 Chinese, 511 South Asian patients). More Chinese patients were prescribed BBs (79.7% vs. 73.1%, p = 0.04) and more South Asian patients were prescribed statins (73.5% vs. 65.2%, p = 0.001). Both Chinese (Odds Ratio [OR] 0.53; 95%CI, 0.39-0.73; p < 0.0001) and South Asian (OR 0.78; 95%CI, 0.61-0.99; p = 0.04) patients were less adherent to ACEI compared to Non-Asian patients. South Asian patients were more adherent to BBs (OR 1.3; 95%CI, 1.04-1.62; p = 0.02). There was no difference in prescribing of ACEI, nor adherence to statins among the ethnicities. Conclusion Despite a higher likelihood of being prescribed evidence-based therapies following AMI, Chinese and South Asian patients were less likely to adhere to ACEI compared to their Non-Asian counterparts.